The role of PECVD hard coatings on the performance of industrial tools - Zarchi, Meysam; Ahangarani, Sharokh; Sanjari, Maryam Zare (Metallurgical and Materials Engineering, 2014)
The advantages of the application of hard coatings, which are well knownfor cutting tools, are to a much lesser extent explored for casting, extrusion, molding and forming tools. Increasing the lifetime of these tools is an important task in surface engineering because of complex loading conditionsand often complicated tool geometry. The plasma-enhanced chemical vapor deposition (PECVD) technique is well suited to deposit hard coatings onto large dies and moulds. The aim of this study was to discuss deposition processes suitable for coating of the often large three-dimensional molds and dies used in metal forming. Furthermore, results obtained using different hard coatings in industrial applications for several case studies like aluminum pressure die-casting; plastics injection molding and sheet metal forming are presented and discussed. For best coating performance, a careful optimization of both substrate pretreatment and coating deposition is necessary. The plasma-enhanced chemical vapor deposition (PECVD) technique shows advantages for these applications because of the high flexibility in pre-treatment using chemical etching and plasma-nitriding, because of its ability to coat large complexly shaped tools and because of the possibility of deposition of low-chlorine containing low-friction coatings. http://dx.doi.org/10.5937/metmateng1401015Z